Sharia Financial Services Products Based on Muḍārabah Contract as a Form of Investment - Sofwan, Camelia (Journal of Economicate Studies, 2025)
This study explores sharia-based investment options, focusing on customer preferences for financial service products that utilize the muḍārabah contract as a form of investment. Employing a qualitative research approach, the data were sourced from scholarly publications related to muḍārabah-based investments. The data, presented in theoretical narratives, were analyzed using a descriptive-interpretive method to identify patterns and implications in Islamic financial practice. The findings reveal that muḍārabah-based investment products primarily operate through Sharia financial institutions, particularly in the form of muḍārabah savings and muḍārabah deposits. These instruments facilitate capital flow between surplus and deficit units in a profit-and-loss sharing framework, offering an ethical and Sharia-compliant investment alternative. This study underscores the importance of muḍārabah in promoting equitable, risk-sharing financial growth within the Islamic financial system.